Responsabilidade social corporativa e gestão de pessoas: uma análise sobre atração e retenção de profissionais qualificados - Costa, Tatiana Gonçalves (Universidade do Vale do Rio dos Sinos, 2020)
With the assumption that qualified professionals are essential sources of competitive advantage and organizational growth, some authors have been discussing the influence of Corporate Social Responsibility (CSR) practices on companies' ability to attract and retain qualified professionals. In parallel, the People Management (PM) area has been responsible for implementing strategies to engage and disseminate actions and values aimed at a socially responsible business culture. In this context, this study's objective was to analyze how CSR policies and practices influence GP in attracting and retaining qualified professionals. The study also explores the descriptions of the generational behavior of qualified professionals. The methodology adopted was a single case study using different data sources, mostly open and semistructured interviews. As an empirical field, a multinational company in the technology sector was chosen, based on its recognition in rankings as a good place to work. The results of the study show that CSR practices are part of the company's business model. Concerning CSR's influence on PM in attracting qualified professionals, data reveals the company's positioning concerning diversity and inclusion in promoting an organizational reputation that presents work free of prejudice in hiring qualified professionals. Concerning retention, data suggests that the possibility of experiencing social practices promotes self-development and engagement and affect socialization and networking. Regarding generational behavior, evidence leads us to understand that CSR inserted in the strategy and conducted organically by employees, is motivated by millennials' generational conduct.
Keywords: Responsabilidade social corporativa; Gestão de pessoas; Atração; Retenção; Gerações; Corporate social responsibility; People management; Attraction; Retention; Generations; ACCNPQ::Ciências Sociais Aplicadas::Administração